Pilot study: the prevalence of use of Complementary and Alternative Medication (CAM) in pregnant and lactating women - A. Rahman, Nur Adilah; Rahmat, Nur Alya Aisyah (2014)
The use of complementary and alternative medicine (CAM) on pregnant and lactating women is rising to this date. Hence, the objective of this cross-sectional study is to determine the prevalence of use of complementary and alternative medication (CAM) in pregnant and lactating women in Hospital Pulau Pinang. A total of 360 women were interviewed using a structured questionnaire. There were 117 mothers (32.5%) who used complementary and alternative medication (CAM) during pregnancy. Among the complementary and alternative medication (CAM) the majority of users (58.1%) used complementary and alternative medication (CAM) during the first trimester of pregnancy. Many of them (49.6%) believed that complementary and alternative medications (CAM) were effective to solve their undesired adverse effect of pregnancy or lactating such as lethargy and hair fall. The family members like parents and siblings (41.0%) were the most common persons who suggested using complementary and alternative medication (CAM). The majority of them (29.9%) used herbs as the complementary and alternative medication (CAM) throughout the pregnancy and lactating. From this research, we will know the percentage of pregnant and lactating women that are using CAM and why they do so. Thus, from our research finding, it will help the healthcare professionals in the future can prepare themselves with knowledge on CAM use on pregnant and lactating women.